Seizing Jerusalem the architectures of unilateral unification - Nitzan-Shifṭan, Alonah (A quadrant book, 2017)
This first architectural history of post-1967 Jerusalem chronicles how architecture, landscape design, urban planning, and everyone from municipal politicians to state bureaucrats, Israeli-born architects to international luminaries, competed to create Jerusalem's new image. Alona Nitzan-Shiftan reveals architecture as an active agent in forming urban and national identity, demonstrating how debates about Zionism affected Jerusalem's built environment in ways that resonate today